Primary external auditory canal cholesteatoma: Pediatric case report - Melo, Marta (2021)
Case report of a 12 year old female child, with complaints of otalgia and left ear otorrhea with 3 months of evolution. Physical examination revealed a polypoid lesion that completely obliterated the external auditory canal (EAC). Computed tomography of the ear showed an extensive soft tissue mass, which occupied and enlarged the EAC, with remodeling and erosion of the walls, aspects compatible with external auditory canal cholesteatoma (EACC). A surgical approach was performed, with canalplasty and complete excision of the cholesteatoma that had an apparent origin in the postero-superior wall of the EAC. There was no evidence of EAC atresia nor stenosis.A primary EACC was assumed. The postoperative period was uneventful and there was no evidence of recurrence at one year.Literature review on the topic.